New exact solutions of the system of equations for the ion sound and langmuir waves by ETEM - Demiray, Seyma Tuluce; Bulut, Hasan (Association for Scientific Research, 2016)
This manuscript focuses attention on new exact solutions of the system of equations for the ion sound wave under the action of the ponderomotive force due to high-frequency field and for the Langmuir wave. The extended trial equation method (ETEM), which is one of the analytical methods, has been handled for finding exact solutions of the system of equations for the ion sound wave and the Langmuir wave. By using this method, exact solutions including the rational function solution, traveling wave solution, soliton solution, Jacobi elliptic function solution, hyperbolic function solution and periodic wave solution of this system of equations have been obtained. In addition, by using Mathematica Release 9, some graphical simulations were done to see the behavior of these solutions.
Keywords: Exact solutions; Extended trial equation method; Mathematica release 9; The system of equations for the ion sound wave and the langmuir wave